Prone positioning for non-intubated spontaneously breathing patients with acute hypoxaemic respiratory failure: a systematic review and meta-analysis. (February 2022) - Fazzini, Brigitta; Page, Alexandria; Pearse, Rupert; Puthucheary, Zudin
Abstract: Background: Prone positioning in non-intubated spontaneously breathing patients is becoming widely applied in practice alongside noninvasive respiratory support. This systematic review and meta-analysis evaluates the effect, timing, and populations that might benefit from awake proning regarding oxygenation, mortality, and tracheal intubation compared with supine position in hypoxaemic acute respiratory failure. Methods: We conducted a systematic literature search of PubMed/MEDLINE, Cochrane Library, Embase, CINAHL, and BMJ Best Practice until August 2021 (International Prospective Register of Systematic Reviews [PROSPERO] registration: CRD42021250322). Studies included comprise least-wise 20 adult patients with hypoxaemic respiratory failure secondary to acute respiratory distress syndrome or coronavirus disease (COVID-19). Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed, and study quality was assessed using the Newcastle–Ottawa Scale and the Cochrane risk-of-bias tool. Results: Fourteen studies fulfilled the selection criteria and 2352 patients were included; of those patients, 99% ( n =2332/2352) had COVID-19. Amongst 1041 (44%) patients who were placed in the prone position, 1021 were SARS-CoV-2 positive. The meta-analysis revealed significant improvement in the P aO2 /FiO2 ratio (mean difference –23.10; 95% confidence interval [CI]: –34.80 to 11.39; P =0.0001; I 2 =26%) after prone positioning. In patients with COVID-19, lower mortality was found in the group placed in the prone position (150/771 prone vs 391/1457 supine; odds ratio [OR] 0.51; 95% CI: 0.32–0.80; P =0.003; I 2 =48%), but the tracheal intubation rate was unchanged (284/824 prone vs 616/1271 supine; OR 0.72; 95% CI: 0.43–1.22; P =0.220; I 2 =75%). Overall proning was tolerated for a median of 4 h (inter-quartile range: 2–16). Conclusions: Prone positioning can improve oxygenation amongst non-intubated patients with acute hypoxaemic respiratory failure when applied for at least 4 h over repeated daily episodes. Awake proning appears safe, but the effect on tracheal intubation rate and survival remains uncertain.